2020
DOI: 10.1038/s41598-020-61737-1
|View full text |Cite
|
Sign up to set email alerts
|

Congruency and reactivation aid memory integration through reinstatement of prior knowledge

Abstract: Building knowledge schemas that organize information and guide future learning is of great importance in everyday life. Such knowledge building is suggested to occur through reinstatement of prior knowledge during new learning, yielding integration of new with old memories supported by the medial prefrontal cortex (mpfc) and medial temporal lobe (MtL). congruency with prior knowledge is also known to enhance subsequent memory. Yet, how reactivation and congruency interact to optimize memory integration is unkn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
5
26
2
Order By: Relevance
“…Besides, we found that subjective reactivation scores were positively related to subsequent long-term memory performance such that higher reactivation of the definition led to more accurate and faster response times in the semantic decision task. These results suggest that participants' responses were associated with the strength of reactivation, which turned out to be a valid predictor of later memory performance (St. Jacques & Schacter, 2013;van Kesteren, Rignanese, Gianferrara, Krabbendam, & Meeter, 2020). All in all, results of Study A reinforce previous findings regarding the positive role of memory retrieval for subsequent memory and also provide new evidence for the specific effect of reactivation on lexical integration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Besides, we found that subjective reactivation scores were positively related to subsequent long-term memory performance such that higher reactivation of the definition led to more accurate and faster response times in the semantic decision task. These results suggest that participants' responses were associated with the strength of reactivation, which turned out to be a valid predictor of later memory performance (St. Jacques & Schacter, 2013;van Kesteren, Rignanese, Gianferrara, Krabbendam, & Meeter, 2020). All in all, results of Study A reinforce previous findings regarding the positive role of memory retrieval for subsequent memory and also provide new evidence for the specific effect of reactivation on lexical integration.…”
Section: Discussionsupporting
confidence: 78%
“…All in all, these results show there is a graded enhancement effect of the reminder according to its level of reactivation, possibly implying differences in the efficiency exerted by the reminders in the process of lexical access. In addition, these results shed light into the importance of metamemory ratings during recall, and constitute a powerful tool to address item variability (van Kesteren, Rignanese, Gianferrara, Krabbendam, & Meeter, 2020).…”
Section: Discussion (Study A)mentioning
confidence: 89%
“…However, since the return to a previous encoding context is a strong retrieval cue (S. M. Smith & Vela, 2001;van Ast, Cornelisse, Meeter, Joëls, & Kindt, 2013;van Ast, Cornelisse, Meeter, & Kindt, 2014), the idea that contextual similarity leads to impaired recall diametrically conflicts with memory integration studies showing that new learning is enhanced by retrieval of original associated memories (Chanales, Dudukovic, Richter, & Kuhl, 2019;Jacoby & Wahlheim, 2013;Schlichting & Preston, 2014;Szpunar, McDermott, & Roediger, 2008;Wahlheim, 2015). Such retrieval can also strengthen existing memories (Karpicke & Roediger, 2008;Koen & Rugg, 2016;Kuhl, Shah, Dubrow, & Wagner, 2010;Oudiette, Antony, Creery, & Paller, 2013;Potts & Shanks, 2012), as well as associations across existing and new memories (so-called inferential memory, van Kesteren, Krabbendam, & Meeter, 2018;van Kesteren, Rignanese, Gianferrara, Krabbendam, & Meeter, 2020;Zeithamova, Dominick, & Preston, 2012). Conceivably, earlier studies may not have found enhancements with contextual similarity, because the employed procedures (list learning in experimental rooms, e.g., Bilodeau & Schlosberg, 1951) did not explicitly promote associations between learning events and a unique environmental context, and thus failed to induce lifelike episodic memories (Tulving, 1972) that consist of what-where-when qualities and a recollective experience during recall (Tulving, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We hoped that these judgment tasks that were unique to each environment, paired with the item-finding and context-initiation action sequences (also unique to each environment), would foster the activation of context-unique associations during encoding. Additionally, we hypothesized that items that were affirmatively judged to be useful in the encoding environment would show a stronger contextchange effectthe idea being that schema-consistent items would be more strongly integrated into the active schema at encoding (Bransford & Johnson, 1972;Spalding et al, 2015;van Kesteren et al, 2013van Kesteren et al, , 2018van Kesteren et al, , 2020 and thus suffer more if that schema were not active at retrieval. The context-initiation action sequences were also performed at the beginning of the retrieval session, making the encoding and retrieval sessions more similar for the "same" condition and more distinctive for the "different" condition.…”
Section: Introductionmentioning
confidence: 99%